PERANCANGAN MAJALAH SIMANIS EDISI PANDUAN PEMELIHARAAN DAN PERAWATAN KUCING - ASMA DEWI, Ir. Drs. Heldi, M.Si., Ph.D., Dra. Lisa widiarti, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Not all of the cat owners know how to treat and take care of the cats correctly. It might cause the cats become sleazy. Meanwhile, the cat magazines with the edition how to treat and take care of the cats are still rarely found in Indonesia. The purpose of